Clinical Holistic Medicine: The Case Story of Anna. I. Long-Term Effect of Childhood Sexual Abuse and Incest with a Treatment Approach - Søren Ventegodt; Birgitte Clausen; Joav Merrick (The Scientific World Journal)
The nervous breakdown of a 22-year-old, young woman was caused by severe sexual abuse in childhood, which was repressed over many years. During therapy, the patient accumulated resources to start the painful integration of these old traumas. Using holistic existential therapy in accordance with the life mission theory and the holistic process theory of healing, she finally was able to confront her old traumas and heal her existence. She seemingly recovered completely (including regaining full emotional range) through holistic existential therapy, individually and in a group. The therapy took 18 months and more than 100 hours of intensive therapy. In the beginning of the therapy, the issues were her physical and mental health; in the middle of the therapy, the central issue was her purpose of life and her love life; and at the conclusion of the therapy, the issue was gender and sexuality. The strategy was to build up her strength for several months, mobilizing hidden resources and motivation for living, before the old traumas could be confronted and integrated. The therapy was based on quality of life philosophy, on the life mission theory, the theory of ego, the theory of talent, the theory of the evil side of man, the theory of human character, and the holistic process theory of healing. The clinical procedures included conversation, philosophical training, group therapeutic tools, extended use of therapeutic touch, holistic pelvic examination, and acceptance through touch was used to integrate the early traumas bound to the pelvis and scar tissue in the sexual organs. She was processed according to 10 levels of the advanced toolbox for holistic medicine and the general plan for clinical holistic psychiatry. The emotional steps she went through are well described by the scale of existential responsibility. The case story of Anna is an example of how even the most severely ill patient can recover fully with the support of holistic medical treatment, making her feel, understand, and let go of her negative beliefs and life-denying decisions.